SambaKodiPi A Personal File Server and Media Center - Nurfauza, Jali; Vincent Meringgai, Birang; Cheah, Wai Shiang; Ahmad Hadinata, Fauzi; Suriati Khartini, Jali (Universiti Teknikal Malaysia (UTEM), 2017)
Conventional file sharing and media viewing usually involve slow and tedious data transfer. This project aims to provide access convenience for sharing data and directviewing of media files by having file server (FS) and media center (MC) capability using Raspberry Pi (RPi). The system consists of several functionalities that were developed through iterative and incremental development. The resulting system has its FS function catered by Samba program and its MC function catered by Kodi program. Direct MC output is on highdefinition television (HDTV). The web-based user interface (WebUI) provides administrative functions for the system, its FS and users management and indirect access to its MC function through web player for all registered users. The system has undergone several testing processes, and it is a working prototype of an economical and feasible file server and media center using RPi. The system can still be improved with other functions and features in the future.